Residents about residency: educational integrity and skill assessment - Fidanza, Andrea; Rallo, Flavia; Mazzoleni, Manuel Giovanni; Giannetti, Alessio; Grasso, Michele; Viola, Federica (Lo Scalpello - Journal, 2022)
In the last few years, as the COVID-19 pandemic put in the spotlight the flaws of the Italian National Health System (INHS), the Italian National Residency Program (NRP) has aroused more and more interest among several stakeholders. The persistent burden on the Welfare System, caused by the systemic shortage of Specialized Practitioners, inevitably influenced the recent major reforms of the NRP, eventually affecting its quality. Within this emergency scenario, the urge to critically analyze the post-graduate educational program and its methods, became impellent. As the Orthopedics and Traumatology Italian Residents Association (AISOT) showed, despite the newly introduced DL Calabria, in 2020, almost 50% of the Orthopedic Residents would not feel comfortable to be challenged as independent specialists. However, the lack of methodological involvement of Residents in daily practice activities, from their Mentors, if matched with the positive feedback provided from residents who, conversely, experienced the DL Calabria conveniences, raised some concerns about the standard of quality of future Orthopedics. Modern times and technologies may allow a more efficient redesign and less nebulous educational methods and goals, and eventually guarantee a Nationwide equality among each Orthopedic School. A shared future with exhaustive objectives and fair opportunities between all Italian Orthopedic Residents is the key to build a righteous collective intelligentsia and harmony between practitioners of a glorious discipline, with ancient roots, such as Italian Orthopedics.